(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Software is the foundation of computer networks, driving everything from data routing to security protocols and network management. This article examines the current landscape of software supply in computer networks, focusing on the development, deployment, and maintenance of network software. We explore challenges such as scalability, security vulnerabilities, and interoperability, and discuss emerging solutions including automation, cloud-native technologies, and zero-trust security models. This study also emphasizes the importance of robust software supply chains in ensuring the reliability and security of modern network infrastructures.